INDICATORS OF BIOELECTRICAL ACTIVITY OF THE PROPER MASSETER MUSCLES WITH THEIR DIFFERENT MASS IN MALES - O.V. Rybalov; Yu.I. Semenenko; P.I. Yatsenko; O.I. Yatsenko; O.S. Ivanytska (Український стоматологічний альманах, 2018)
The biomechanic disorders of entire masticatory complex underlie the formation of extraarticular functional disturbances of the temporomandibular joint. The available data in literature on electromyographic study of the masseter muscular apparatus are sometimes controversial even for healthy individuals. That is why it is reasonable to search solutions of problems on the objectification of the leading characteristics of bioelectric activity of the masseter muscles for people having no dental pathologies in spite of adequate comparison them to various diseases of the muscle and joint complex for their clinical and pathogenetic treatment.